Research on the optimization of financing scheme of long-term care insurance in China based on system dynamics simulation - Zhang, Liangwen; Fu, Sijia; Wang, Yifan; Fang, Ya (Frontiers in Public Health, 2022)
Objective: The aging population in China highlights the significance of long-term care insurance (LTCI). This study provides policy suggestions for China to establish a sustainable LTCI financing mechanism by predicting the trend of funds balance, screening the appropriate financing scheme. Method: A System Dynamics model (SDM) of LTCI funds was constructed by clarifying the current situation and its main influencing factors of revenue and expenditure of LTCI funds in China. Also, through literature research and expert consultation, we found the intervention goals and predicted the changing trend of LTCI funds balance from 2020 to 2050 under different intervention schemes. Results: The SDM of LTCI financing passes dimensional consistency test, structural test and historical test. Therefore, it can objectively reflect the structure and behaviour of the financing system. It is found that the factors affecting the revenue and expenditure system of LTCI funds mainly include economic factors, demographic factors and other factors. By adjusting three intervention indicators: individual payment rate, reimbursement proportion and severe disability rate, this study produces 45 financing combination schemes. By comparing the change trend of LTCI funds balance under different intervention schemes, according to the screening principle, five better financing schemes are finally selected. These five financing schemes have no deficit and excessive balance in the forecast period, which is in line with the principle of sustainability. It can provide reference for the selection of financing schemes in pilot areas. Discussion: This study has optimized the policy of LTCI financing mechanism, determined the suitable LTCI participants, financing channels and levels, and screened out the suitable LTCI financing policy optimization scheme for China. By appropriately increasing the individual payment rate, strengthening the disability intervention of the elderly, formulating scientific and objective disability evaluation standards, and finally establishing a dynamic financing adjustment mechanism of LTCI. This study can provide a basis for the scientific formulation of LTCI financing mechanism in China, and provide a reference for developing countries to establish a sustainable LTCI.